2022
DOI: 10.3847/1538-4357/ac9798
|View full text |Cite
|
Sign up to set email alerts
|

Four Eccentric Mergers Increase the Evidence that LIGO–Virgo–KAGRA’s Binary Black Holes Form Dynamically

Abstract: The growing population of compact binary mergers detected with gravitational waves contains multiple events that are challenging to explain through isolated binary evolution. Such events have higher masses than are expected in isolated binaries, component spin tilt angles that are misaligned, and/or nonnegligible orbital eccentricities. We investigate the orbital eccentricities of 62 binary black hole candidates from the third gravitational-wave transient catalog of the LIGO–Virgo–KAGRA Collaboration with an a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 140 publications
1
8
0
Order By: Relevance
“…In summary, BBHs assembled in dense star clusters can explain the mass, effective spin, and rate of GW191109, unlike isolated binary evolution. Also note that our interpretation of GW191109 as having a dynamical origin is consistent with the findings in Romero-Shaw et al (2022). In this study, they used a reweighting method (Payne et al 2019;Romero-Shaw et al 2019) to calculate the eccentricity posterior probability distribution and found 72.19% of its posterior support at an eccentricity above 0.05 and 62.63% above 0.1.…”
Section: Dynamics In Dense Star Clusterssupporting
confidence: 85%
“…In summary, BBHs assembled in dense star clusters can explain the mass, effective spin, and rate of GW191109, unlike isolated binary evolution. Also note that our interpretation of GW191109 as having a dynamical origin is consistent with the findings in Romero-Shaw et al (2022). In this study, they used a reweighting method (Payne et al 2019;Romero-Shaw et al 2019) to calculate the eccentricity posterior probability distribution and found 72.19% of its posterior support at an eccentricity above 0.05 and 62.63% above 0.1.…”
Section: Dynamics In Dense Star Clusterssupporting
confidence: 85%
“…However, we may still be overestimating the contribution from GCs, because multiple other formation channels and environments can produce BBH mergers with 𝜒 eff < 0. In the future, we can use more specific criteria to isolate the GC contribution to the merger rate, including, for example, the BBH population distribution of orbital eccentricity (Samsing 2018;Rodriguez et al 2018a;Zevin et al 2019;Arca Sedda et al 2021), which can be used to measure the fraction of BBHs assembled in GCs (Zevin et al 2021b;Romero-Shaw et al 2022), and the rate of hierarchical mergers (Rodriguez et al 2018b;Kimball et al 2021;Gerosa & Fishbach 2021) as inferred from the distribution of spin magnitudes (Fishbach et al 2017;Baibhav et al 2020;Fishbach et al 2022). Given robust predictions for the BBH population distribution of eccentricity, spin magnitudes, and/or masses as a function of GC properties, we may incorporate these additional BBH observables into our inference, and improve our constraints on GC properties.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons to the observed BH masses, spins, and merger rate indicate that a sizable fraction of the observed mergers may indeed originate in AGN disks (Tagawa et al 2021a;Gayathri et al 2021;Ford & McKernan 2022). The AGN channel could also explain some of the peculiar detections, such as those with a high mass (Tagawa et al 2021a;Gayathri et al 2023) and possibly high eccentricity (Tagawa et al 2021b;Gayathri et al 2022;Romero-Shaw et al 2022;Samsing et al 2022; but see Romero-Shaw et al 2020.…”
Section: Introductionmentioning
confidence: 93%